2011
DOI: 10.1007/s10384-011-0048-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rho-associated protein kinase inhibitors Y-27632 and Y-39983 on isolated rabbit ciliary arteries

Abstract: We concluded that Y-27632 and Y-39983 relaxed isolated rabbit ciliary artery segments in vitro. The mechanism of relaxation was not dependent on endothelial-derived factors such as nitric oxide (NO) or prostacyclin, nor was it dependent on changes in intracellular Ca(2+) concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 32 publications
(45 reference statements)
2
17
1
Order By: Relevance
“…Clinical trials are currently in progress for the treatment of normotensive glaucoma, with methods that increase blood flow in the optic nerve, such as medications that inhibit spasm of the vessels to the eye or that raise systemic blood pressure, removing the plaque in the carotid artery if it exists, or using a catheter with a balloon inserted through the artery in plaques located in smaller or harder‐to‐reach areas, or using Rho‐associated coiled coil‐forming protein kinase (ROCK) inhibitors (Y‐27632 and Y39983) to relax rabbit ciliary arteries (Watabe et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials are currently in progress for the treatment of normotensive glaucoma, with methods that increase blood flow in the optic nerve, such as medications that inhibit spasm of the vessels to the eye or that raise systemic blood pressure, removing the plaque in the carotid artery if it exists, or using a catheter with a balloon inserted through the artery in plaques located in smaller or harder‐to‐reach areas, or using Rho‐associated coiled coil‐forming protein kinase (ROCK) inhibitors (Y‐27632 and Y39983) to relax rabbit ciliary arteries (Watabe et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…16 Although conjunctival hyperemia was seen in more than half of the patients treated with AR-13324, its vasodilatory activity was transient, as evidenced by the lower incidence of conjunctival hyperemia as scored by biomicroscopic examination in the morning relative to the incidence of hyperemia in the adverse event reports, which included patient-reported eye redness after dosing in the evening. The biomicroscopy examinations also revealed that the incidence of hyperemia decreased throughout the study for AR-13324.…”
Section: Discussionmentioning
confidence: 99%
“…27 The conjunctival hyperemia observed in netarsudil/latanoprost FDC-treated and netarsudil-treated patients is possibly caused by the vasodilatory effects of ROCK inhibition. [28][29][30][31] Conjunctival hemorrhages were observed intermittently via biomicroscopy in patients treated with netarsudil/ latanoprost FDC or single-agent netarsudil and generally resolved with continued dosing. Cornea verticillata, which is a collection of lipid microdeposits localized to the corneal epithelium, was reported in < _5% of netarsudil/latanoprost FDC-treated and netarsudiltreated patients.…”
Section: In the Primary Efficacy Analysis Of This Study Ofmentioning
confidence: 99%